Something of a Girls Studies Reader?. Issue 3 (1st December 2021) - Mitchell, Claudia
Abstract : Sometimes the evolution of an open call issue of Girlhood Studies results in something of a girls studies reader unto itself. Since this issue is packed full of criss-crossing themes based on work in several countries—Canada, Iceland, India and the US—there is just no room for editorial commentary. In its inclusion of works on intersectional feminisms and feminist and Indigenous-led critique to school-based and intergenerational interventions and the power of the visual, this issue is something of such a reader.